Indoor Positioning Based on ROS Using an Ultra- Wideband System - YUNITA, TRASMA; RIFA’I, AFAF FADHIL; RIDWAN, MUHAMMAD; SURYATINI, FITRIA; BUDIYARTO, ARIS (Institut Teknologi Nasional, Bandung, 2025)
Numerous technologies employ indoor positioning applications, including Ultrawideband (UWB) technology that requires excellent accuracy. This research aims to enhance indoor location accuracy in UWB technology with the NodeMCU-UWBBU01 module by integrating a two-way ranging algorithm, moving average technique, and trilateration. The distance between two modules can be determined using the two-way ranging algorithm's Time of Flight (ToF) signal. The moving average approach filters the ToF signal processed on the Robotic Operating System platform for robot movement. The trilateration method converts the distance into position coordinates as the end output. In static and dynamic accuracy assessments, the maximum error in measurement findings is 4.3% within 50 cm to 600 cm. In evaluating coordinate reading accuracy, the mean error is 1.2% on the X-axis and 3.13% on the Y-axis.